Sustainability Accounting and Governance in MSMEs: A Qualitative Study in Banten, Indonesia - Sri Lestari (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2026)
Micro, small, and medium enterprises (MSMEs) play a strategic role in economic and social development in Indonesia; however, sustainability accounting and governance practices within this sector remain insufficiently understood from a contextual perspective. This study aims to explore how MSMEs in Banten Province conceptualize and integrate sustainability accounting and governance in their daily operations. A qualitative interpretive case study approach was employed, using in-depth interviews, observations, and document analysis involving MSME owners and managers. The findings reveal that sustainability accounting is practiced informally and pragmatically, focusing on business continuity, social relationships, and ethical responsibility rather than formal sustainability reporting. Governance practices are relational and value-based, supported by trust, family involvement, and local wisdom. The novelty of this study lies in framing sustainability accounting and governance as integrated, socially embedded practices that reflect the lived realities of MSMEs in a developing economy. The findings reveal that sustainability accounting is practiced informally and pragmatically, emphasizing business continuity, social relationships, and ethical responsibility rather than formal sustainability reporting. Governance practices are relational and value-based, grounded in trust, family involvement, and local wisdom. Theoretically, this study extends sustainability accounting and governance literature by challenging corporate-centric assumptions and demonstrating how sustainability is socially constructed and embedded in everyday practices of MSMEs in developing economies. Practically, the findings offer insights for policymakers and development agencies to design context-sensitive sustainability frameworks and capacity-building programs aligned with MSMEs’ lived realities rather than imposing rigid reporting requirements.